Galesong Youth Startup Training Based on Waste Management through the Less Contact Economy - Hendra Jaya; Sapto Haryoko; Sutarsi Suhaeb; Sabran; Mustamin; Purnamawati; Riana T. Mangesa; Anita C. Dewi; Ridwansyah (Asian Journal of Community Services, 2023)
The objectives of the PKM activities are: 1) Carry out the waste processing (Collect, Recycle, Utilize); 2) waste management, marketing, and packaging materials. The PKM activity is Management Improvement through Waste management) starting with a Website-based Marketing system. Modules and Implementation Manual Provided to Partners to make it easier to understand. To measure the effectiveness of training activities by evaluating the implementation of training. The PKM training program through the DRPM grant can run well in post-pandemic situations and conditions in Takalar District, North Galesong District, and Aeng Batu-batu Village. Several programs have been adjusted, such as Mentoring activities, Technical Guidance, and face-to-face training, which are conditioned according to the post-Covid-19 health protocol. Partners already know about: (1). Implementing the management of fuel oil products originating from plastic waste; and (2). They are implementing handicraft products from plastic waste with high selling value